ANALISIS KESALAHANPENGGUNAAN RAGAM BAHASA HORMATKEIGOPADA MAHASISWA TINGKAT IIIPRODI PENDIDIKAN BAHASA JEPANG FKIPUNIVERSITAS RIAU - Qodri Nela Antani; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Keigo is a honorific terms in Japanese language, grammar and the concept of its use is quite complicated so it becomes a challenge for students to master it well.However, the function of the various keigoin Japanese society is very wide, especially in the occupations where there is a relationship between superiors and subordinates.Therefore, as a Japanese language learner, mastering keigo is an important thing.There are two problems of formulations in this study, there are how is the miscomprehension of the forms of Keigo on Juniors (3rd year students) of the Japanese Department of Education (FKIP) Riau University, and Few of Factors that influencing the miscomprehension of the forms of keigo by Juniors of FKIP Riau University.The data of this study were taken from the results of tests and questionnaires from Juniors of Japanese language students.The results of the data are collected, checked, calculated, compiling in the form of tables and compiling frequency and presentation of test answers and questionnaires, then analyzed.Through this research, it is known that the level of ability of Juniors of Japanese language students in the use of keigo is very low.These results are stronglybecause the understanding and mastery of keigo that is not optimal both in terms of grammar and application in daily conversation.The lack of comprehending and rarely usage of the language are ones of the influenced factors that make students forgetting the structures and leading them to miscomprehension.KeyWords:Error Analysis, Japanese Language, Keigo